Charity donation: intentions and behaviour. Issue 1 (2nd February 2015) - Kashif, Muhammad; Sarifuddin, Syamsulang; Hassan, Azizah
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to test the extended theory of planned behaviour (TPB) model to investigate money donation intentions and behaviour. Furthermore, the applicability of an extended TPB model is tested for the first time in a collectivist culture. Design/methodology/approach – The data have been collected from 221 people living in the city of Kuala Lampur through a questionnaire based on extended TPB model. The data have been analysed through employing structural equation modelling (SEM) procedures to extract meaningful conclusions. Findings – The results depict an excellent fit to the extended TPB model. The past behaviour, injunctive norms, and intentions to donate positively contribute towards actual behaviour to donate money. Attitude, self-reported behaviour, descriptive norms, and moral norms do not significantly contribute to intentions to donate money. Practical implications – Managers of charitable organisations are struggling to attract customers who can actively donate money in response to various fundraising campaigns. This study will provide some useful strategies to help managers in attracting and retaining customers for life. Originality/value – Research studies performed to investigate money donation intentions and behaviour are scarce where current research fills this knowledge gap by presenting a developing country perspective. In addition to that, extended TPB model to investigate money donation intentions and behaviour has never been refuted through SEM procedures.